Analysis Slang Words In The Fast Five Movie - Ida Bagus Dwitiya Prajnyawedanta; I Gusti Agung Istri Aryani; Galuh Febri Putra (CV. ULIL ALBAB CORP, 2024)
This study aims to determine the types and function of slang words found in Fast Five movie. In this study, the researchers analyzed the types of slang words based on the theory from Allan and Burridge (2006). This study employed a qualitative research approach based on Creswell's (2007) theory. The data was gathered using the observation approach, which involved downloading the film, watching it, and then noting any slang terms that were used. The data source of this study was taken from the movie of Fast Five, directed by Justin Lin and written by Chris Morgan. Based on the result, there were fresh and creative type of slang, flippant type of slang, imitative type of slang, clipping type of slang.